KETANGGUHAN MENTAL STUDENT-ATHLETE BOLA BASKET: MENGANALISIS SUMBER DAN PERANAN DUKUNGAN SOSIAL - Sopacua, Theogratia Antonio; Novanto, Yusak (Jurnal Psikologi : Media Ilmiah Psikologi, 2023)
The Honda DBL Banten series is the biggest basketball event in Indonesia. Mental toughness has an important role in student-athlete performance. Mental toughness is a collection of values, attitudes, behaviors, and emotions that enable a person to be able to overcome obstacles, difficulties or pressure experienced. One of the factors that influences mental toughness is social support. The research was conducted using a quantitative correlational method using the Sports Mental Toughness Questionnaire (SMTQ) and the Multidimensional Scale of Perceived Social Support (MSPSS). The author collected data from 95 students from five senior high schools in Tangerang surrounding area. The results of this study show a relationship between social support and mental toughness. The regression test also shows that there is a significant effect of social support on mental toughness, especially from their significant others.